Molecular Dynamics Simulations on Influence of Defect on Thermal Conductivity of Silicon Nanowires - Li, Hao; Rui, Qiancheng; Wang, Xiwen; Yu, Wei (Frontiers in Energy Research, 2021)
A non-equilibrium molecular dynamics simulation method is conducted to study the thermal conductivity (TC) of silicon nanowires (SiNWs) with different types of defects. The impacts of defect position, porosity, temperature, and length on the TC of SiNWs are analyzed. The numerical results indicate that SiNWs with surface defects have higher TC than SiNWs with inner defects, the TC of SiNWs gradually decreases with the increase of porosity and temperature, and the impact of temperature on the TC of SiNWs with defects is weaker than the impact on the TC of SiNWs with no defects. The TC of SiNWs increases as their length increases. SiNWs with no defects have the highest corresponding frequency of low-frequency peaks of phonon density of states; however, when SiNWs have inner defects, the lowest frequency is observed. Under the same porosity, the average phonon participation of SiNWs with surface defects is higher than that of SiNWs with inner defects.